On the motives and needs for work beyond age 65: Comparing voluntary workers versus agency workers - Nicole Torka; Ivy Goedebebure; Inge van Ewijk; Jan Kees Looise (Zeitschrift für Personalforschung (ZfP), 2012)
Much has been written about older workers, including how to adequately manage a more mature workforce. Currently, the bulk of research concentrates on the push-pull factors for early retirement vs. the continuation of work life until the pensionable age. This article focuses on a different and rarely investigated group and explicitly addresses an issue up to now overlooked: for those who continue work beyond the age at which full government pension benefits are available (i.e., post-retirement workers), is the meaning of work related to their employment status? To answer this question we compared the work motives of Dutch volunteers and agency workers aged 65 years (i.e., the official Dutch pensionable age) and older. Contrary to the presumptive prevailing common convictions, we found that for post-retirement agency workers financial motives or needs seem less important than personal motives, and the employment status itself is not a good indicator for decision- making on human resource practices. We conclude that for these 'indisputable seniors' the satisfaction of esteem needs through work remains unremitting, and may even be increasingly important as time goes by. – – Im vorliegenden Artikel wird untersucht, ob ehrenamtliche MitarbeiterInnen und LeiharbeiterInnen im Alter von 65 Jahren und älter ihrer Arbeitstätigkeit mit verschiedenen Motiven und Bedürfnisse begegnen. Durch demografische Entwicklungen sind Arbeitgeber zunehmend auf ältere Beschäftigte angewiesen. Auch die Erhöhung des offiziellen Rentenalters hat zur Folge, dass Arbeitgeber und insbesondere das Personalmanagement sich der Frage stellen müssen, wie ältere Arbeitnehmer für den Betrieb erhalten bleiben können. Dabei ist die Einsicht in die Motive und Bedürfnisse dieser Arbeitnehmer essentiell: Nur wenn Arbeitgeber adäquat auf diese reagieren, kann eine zufriedenstellende Arbeitsbeziehung realisiert werden. Nach Mor-Barak (1995) unterscheiden wir finanzielle, soziale, persönliche und 'generative' Bedürfnisse. Die quantitative Studie unter niederländischen ehrenamtlichen MitarbeiterInnen (n = 54) und LeiharbeiterInnen (n = 178) zeigt, dass sogar für die Letztgenannten finanzielle Motive weniger wichtig sind als persönliche. Desweiteren zeigen die Ergebnisse keine signifikanten Unterschiede zwischen ehrenamtlichen MitarbeiterInnen und LeiharbeiterInnen in Bezug auf soziale, persönliche und generative Motive. Basierend auf diesen Ergebnissen wird diskutiert, ob die vertragliche Arbeitsbeziehung als Entscheidungskriterium für das Personalmanagement dienen kann und sollte.
Keywords: M00; M1; M12; M50; M54; 650; post-retirement workers; volunteers; agency workers; needs; motives; the Netherlands; Ältere Arbeitskräfte; Altersgrenze; Ehrenamtliche Arbeit; Leiharbeit; Leistungsmotivation; Vergleich; Niederlande